2009
DOI: 10.1159/000272023
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T Homozygous Mutation in a Patient with Pigmentary Glaucoma and Central Retinal Vein Occlusion

Abstract: Purpose: We present the rare case of a young male patient with asymmetric ocular findings: pigmentary ocular hypertension associated with nonischemic central retinal vein occlusion (CRVO) in the right eye and pigmentary glaucoma (PG) with progressive glaucomatous optic damage in the left eye. Patients and Methods: A 31-year-old man showed nonischemic CRVO in the right eye and the clinical triad of pigment dispersion syndrome in both eyes, however more marked in the left eye. Best-corrected visual acuity was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…These data correlate with the ganglion cell losses noted here in cbs +/− mice and reported earlier (Ganapathy et al ., 2009; Ganapathy et al ., 2011). Within the past few years there have been several clinical studies reporting elevated homocysteine associated with various forms of glaucoma (Tranchina et al ., 2011; Turgut et al ., 2010; Jaksic et al ., 2010; Micheal et al ., 2009; Clement et al ., 2009). It will be informative to determine whether mutations of CBS and genes encoding other proteins involved in homocysteine metabolism contribute to some forms of glaucoma or optic nerve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data correlate with the ganglion cell losses noted here in cbs +/− mice and reported earlier (Ganapathy et al ., 2009; Ganapathy et al ., 2011). Within the past few years there have been several clinical studies reporting elevated homocysteine associated with various forms of glaucoma (Tranchina et al ., 2011; Turgut et al ., 2010; Jaksic et al ., 2010; Micheal et al ., 2009; Clement et al ., 2009). It will be informative to determine whether mutations of CBS and genes encoding other proteins involved in homocysteine metabolism contribute to some forms of glaucoma or optic nerve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction was not progressive, however, and no difference was noted when mice were tested at 13 weeks of age. Although VEPs were not recorded, it is important to note that several cases of MTHFR mutations and visual defects associated with diabetic retinopathy, anterior ischemic optic neuropathy and glaucoma have been reported (Maeda et al ., 2006; Felekis et al ., 2010; Jaksic et al ., 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these cases, CRVO occurs without the presence of the typical risk factors, and a comprehensive workup is warranted [2]. Unusual causes for CRVO in young patients include hypercoagulability states, collagen vascular diseases, lymphoproliferative disorders, malignant hypertension, medications (most notably oral contraceptives and isotretinoin), and trauma [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. A recent study has demonstrated that hyperlipidemia and hyperhomocysteinemia were the most significant risk factors for CRVO in patients under 40 [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ectopia lentis is a major ocular manifestation in homocystinuria. 2 A number of pathological conditions affecting retina have also been linked to hyperhomocysteinemia, such as glaucoma (primary and secondary open-angle glaucoma, exfoliation glaucoma, pigmentary glaucoma), [3][4][5] macular degeneration, maculopathy and retinal degeneration, [6][7][8] and diabetic retinopathy. 9,10 Elevated plasma homocysteine is a potential risk factor for the development of premature occlusive atherosclerosis in humans 2 ; and clinical investigations provide strong evidence that hyperhomocysteinemia is a risk factor for retinal vascular diseases, including central retinal vein occlusion, branch retinal vein occlusion, and central retinal artery occlusion.…”
mentioning
confidence: 99%